2019
DOI: 10.1093/mnras/stz627
|View full text |Cite
|
Sign up to set email alerts
|

SITELLE: an Imaging Fourier Transform Spectrometer for the Canada–France–Hawaii Telescope

Abstract: We present an overview of SITELLE, an Imaging Fourier Transform Spectrometer (iFTS) available at the 3.6-meter Canada-France-Hawaii Telescope. SITELLE is a Michelson-type interferometer able to reconstruct the spectrum of every light source within its 11 field of view in filter-selected bands of the visible (350 to 900 nm). The spectral resolution can be adjusted up to R = 10 000 and the spatial resolution is seeinglimited and sampled at 0.32 per pixel. We describe the design of the instrument as well as the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…The ILS function for SITELLE is a pure cardinal sine (sinc) function. The FWHM of the sinc function is known and fixed since it depends only on the sampling and the maximum optical path displacement of the interferogram scan (Martin et al 2016;Drissen et al 2019). As shown in the work of Martin et al (2016), when natural line broadening is observed, a sinc convolved with a Gaussian function can be used to properly recover the line parameters.…”
Section: Data Reduction and Calibrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ILS function for SITELLE is a pure cardinal sine (sinc) function. The FWHM of the sinc function is known and fixed since it depends only on the sampling and the maximum optical path displacement of the interferogram scan (Martin et al 2016;Drissen et al 2019). As shown in the work of Martin et al (2016), when natural line broadening is observed, a sinc convolved with a Gaussian function can be used to properly recover the line parameters.…”
Section: Data Reduction and Calibrationsmentioning
confidence: 99%
“…Multiple instruments (i.e. Integral Field Spectrographs ; IFS, Imaging Fourier Transform Spectrograph ; IFTS, and Fabry-Perot) have been implemented for this purpose in the visible/near-infrared, most notably the Spectroscopic Areal Unit for Research on Optical Nebulae (SAURON, Bacon et al 2001), Fabry-Perot instruments at the Observatoire de Haute-Provence (Garrido et al 2002) and the Observatoire du Mont-Mégantic (Hernandez et al 2003), the Infrared Spectrograph on the Spitzer Space Telescope (IRS, Houck et al 2004), the Potsdam Multi-Aperture Spectrophotometer -fiber Package (PMAS-PPAK, Roth et al 2005), the Visible Integral-Field Replicable Unit Spectrographs prototype (VIRUS-P, Hill et al 2008), the Multi Unit Spectroscopic Explorer (MUSE, Laurent et al 2006;Bacon et al 2010), the Sydney-AAO Multi-object Integral Field Spectrograph (SAMI, Bryant et al 2012), the Sloan Digital Sky Survey IV (SDSS-IV, Drory et al 2015), and the Spectro-Imageurà Transformée de Fourier pour l'Étude en Long et en Large des raies d'Émission (SITELLE, Brousseau et al 2014;Drissen et al 2019). Many other instruments with integral-field capabilities are currently being developed, e.g.…”
mentioning
confidence: 99%
“…NGC 3344 was observed in March 2016 (RUNID: 16AH41; PI: R.P. Martin) with the imaging Fourier transform spectrometer (iFTS) SITELLE (Drissen et al 2010(Drissen et al , 2019 installed on the 3.6-m Canada-France-Hawaii Telescope (CFHT). With a large 11 × 11 field of view (FoV) and a seeinglimited spatial resolution sampled at 0.32 , SITELLE allows us to obtain more than 4 million spectra in the wavelength range from 350 to 900 nm.…”
Section: Observationmentioning
confidence: 99%
“…ORBS is an automatic data reduction software designed for iFTS data obtained with SITELLE freely available on the web 2 . ORBS follows in a few steps to transform the interferogram cubes (from the two cameras) into a spectral datacube for each filter (see Drissen et al 2019). First, the standard CCD image calibrations are applied, including the bias subtraction, the flat-field correction, and the cosmic rays removal.…”
Section: Data Reduction and Lines Fittingmentioning
confidence: 99%
“…The data presented here consist of three multispectral data cubes obtained with the optical imaging Fourier Transform Spectrometer (iFTS), SITELLE, attached to the 3.6-meter Canada-France-Hawaii Telescope (Drissen et al 2019). SITELLE delivers multispectral cubes covering a 11 ×11 field-of-view, sampled with 0.32 pixels, covering specific bandpasses of the visible band using filters .…”
Section: Observationsmentioning
confidence: 99%